Pengaruh Jenis Bahan Batang Pisang dan Bentuk Media Tanam terhadap Karakteristik Media Tanam dan Pertumbuhan Tanaman Kangkung - Muhammad Diarnanda Surya Pratama; Sumiyati; I Wayan Widia (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2024)
Banana stems have the potential to be used as organic growing media which can facilitate agricultural activities with the application of a hydroponic system. This study aims to determine the physical characteristics of the planting medium resulting from the utilization of banana stems and the effect of the ty pe of banana stem material on growth of water spinach. This study used a randomized block design (RBD) with two treatment factors, namely the type of banana stem material ((A1) true stem, (A2) pseudo stem, (A3) a combination of true and pseudo stem) and th e final form of planting medium ((B1) powdered and (B2) print). This study consisted of 6 treatment combinations with each treatment being repeated 3 times, so that 18 experimental units were obtained. Parameters observed were density, field capacity, pH, number of leaves, plant height, leaf width, and leaf color. The results showed that the planting medium for banana stems had a field capacity value of between 51.54% - 62.91% with a pH value in the range of ideal pH values, namely between 5.93 and 6.23, an d the ideal density for stem growing media original in printed form (A1B2) with a value of 0.43 g/cm3. The highest number of leaves was produced by the original stem planting medium in mold form (A1B2) with an average value of 10, the highest leaf width wa s produced by the pseudo stem planting medium in the form of powder (A2B1), and the highest leaf color was produced by the original stem planting medium in the form of mold (A1B2) and pseudostem growing media in powder form (A2B1) with an average value of 4.